Kelp gametophyte recruitment in articulated coralline algae of the San Juan Islands - Bolinger, Greta; Oetterer, Alexis; Winter, Jordan (My University, 2021)
Kelp species dominate rocky intertidal communities in the Salish Sea and overlap in distribution with a diverse array of articulated coralline algal species. Little is known about the microscopic gametophyte phase of kelp’s biphasic life cycle. Reproductive success and maturity of both life phases is crucial to kelp persistence, and it has been suggested that coralline algae may play a role in kelp gametophyte settlement and recruitment. To test whether Hedophyllum sessile gametophytes settle in the genicula of coralline algae species (Bossiella plumosa, Corallina vancouveriensis, Calliarthron tuberculosum), we collected coralline samples near H. sessile populations and examined their genicula under a microscope. Those assumed to have brown algal gametophytes underwent DNA extraction, amplification, and PCR using the universal plastid amplicon (UPA) and internal transcribed spacer (ITS) regions. Samples that amplified with ITS primers were sequenced but results were inconclusive. To complement the field study, a tank experiment was used to investigate Alaria marginata spore settlement. One week after spores were released into treatment jars (control, algae+spores, algae, autoclaved algae+spores), thalli and settlement plates were examined for gametophyte recruitment. We extracted and amplified DNA from those with growth, performed PCR using the UPA and ITS regions, and sequenced those that amplified. The control jar with spores and no algae contained the most actively-growing and developed gametophytes, while the jars with coralline algae had underdeveloped or dead spores. Future studies should investigate whether coralline toxins may inhibit settlement and recruitment of algae in coralline genicula.
Keywords: Bossiella plumosa; Calliarthron tuberculosum; Corallina vancouveriensis; coralline algae; Hedophyllum sessile